Evaluation Effect of COVID -19 Vaccines on Alopecia Areata: Efek Evaluasi Vaksin COVID -19 pada Alopecia Areata - Marwah S. Kadhim; Layth Hussein Hadi Alshaibah; Roaa Abid Jaythoom (Academia Open, 2024)
This study investigates the impact of COVID-19 vaccination on Alopecia Areata (AA) severity, particularly focusing on gender differences. Data from 65 AA patients (30 vaccinated, 35 unvaccinated) and 1,602,596 healthy controls were analyzed. Physical examinations, laboratory tests, and Severity of Alopecia Tool (SALT) scores were used. Results showed a significant increase in AA severity among vaccinated individuals, especially males, with Pfizer's vaccine having a stronger effect post-second dose. These findings highlight the need for continued research and monitoring of AA post-COVID-19 vaccination. Highlight: Severity Rise: COVID-19 vaccination linked to increased Alopecia Areata severity, especially in males. Pfizer's Impact: Second dose shows stronger Alopecia Areata association than AstraZeneca. Continued Monitoring: Emphasizes need for ongoing research on vaccine-autoimmune disorder interactions. Keyword: Alopecia Areata, COVID-19 Vaccination, Gender Differences, Severity, Monitoring